Systematic Literature Review on the Determinants of Tax Avoidance: Based on Financial Analysis (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2026)
State finances rely heavily on tax revenues, yet tax avoidance remains a persistent obstacle that can reduce government income. This practice is commonly associated with internal corporate conditions. Therefore, this research examines how profitability, leverage, firm size, and capital intensity relate to tax avoidance behavior. Employing a descriptive design with a Systematic Literature Review (SLR), the study evaluates ten empirical articles published between 2021 and 2025 in Sinta and Scopus indexed journals. The analysis indicates that the influence of these internal factors varies across studies. Profitability and leverage demonstrate contradictory effects, as strong earnings and higher debt may stimulate aggressive tax planning through tax shields, but may also restrain avoidance to preserve corporate image. Firm size likewise presents inconsistent results due to regulatory and public attention. In contrast, capital intensity generally shows minimal influence because investments in fixed assets are directed toward operational efficiency. These findings provide valuable considerations for policymakers to strengthen tax deduction regulations and encourage responsible corporate tax compliance.